Integrating Islamic Values and Madurese Local Wisdom in Early Childhood Financial Literacy: Evidence from a Qualitative Multi-Site Case Study - Astuti, Ria; Ardhana Reswari; Muammar Qadafi; Fadilah; Selfi Lailiyatul Iftitah; Luthfatun Nisa' (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – Financial literacy in Indonesia remains uneven, while early childhood financial education tends to emphasize cognitive skills and marginalize religious and cultural dimensions, particularly in Muslim-majority contexts. This study examines the integration of Islamic values and Madurese local wisdom through transformative learning in early childhood financial literacy education. Design/methods/approach – This qualitative multi-site case study involved 15 participants from two Islamic kindergartens in East Java, comprising eight teachers, two principals, and five parents. Data were collected over six months through non-participatory observation, semi-structured interviews, and document analysis. Data analysis followed Braun and Clarke’s reflexive thematic analysis. Trustworthiness was enhanced through methodological triangulation, member checking, and peer debriefing. Findings – The analysis identified three interrelated themes. The first concerns a pedagogical paradigm shift from teacher-centered to student-centered learning, mediated by the use of local wisdom as experiential learning resources, through the Beyond Centers and Circle Time model. The second theme highlights experiential entrepreneurship development through activities such as cooking classes, Market Day programs featuring Madurese products, and structured charitable practices. The third theme addresses the integration of values-based financial literacy, in which Islamic economic principles, including halal–haram considerations, charity, and social responsibility, are embedded in everyday financial learning activities. Across these themes, implementation was characterized by variation in children’s understanding, ongoing teacher mediation, and developmental constraints. Research implications/limitations – The findings indicate that values-integrated transformative learning can strengthen early childhood financial literacy by connecting economic concepts with ethical and cultural meanings. However, generalizability is limited by the small sample, Madurese cultural context, six-month duration, and qualitative design. Practical implications – Early childhood financial literacy in Muslim-majority settings may be enhanced through integrating Islamic values and local culture, supported by teacher capacity building, family–school collaboration, and pedagogical flexibility. Originality/value – This study contributes to values-integrated financial literacy and transformative pedagogy by showing that ethical, cultural, and economic learning develops through negotiated classroom practices rather than linear processes, with relevance across diverse sociocultural contexts.